RNA Interference-Based Forest Protection Products (FPPs) Against Wood-Boring Coleopterans: Hope or Hype? - Joga, Mallikarjuna Reddy; Mogilicherla, Kanakachari; Smagghe, Guy; Roy, Amit (Frontiers in Plant Science, 2021)
Forest insects are emerging in large extension in response to ongoing climatic changes, penetrating geographic barriers, utilizing novel hosts, and influencing many hectares of conifer forests worldwide. Current management strategies have been unable to keep pace with forest insect population outbreaks, and therefore novel and aggressive management strategies are urgently required to manage forest insects. RNA interference (RNAi), a Noble Prize-winning discovery, is an emerging approach that can be used for forest protection. The RNAi pathway is triggered by dsRNA molecules, which, in turn, silences genes and disrupts protein function, ultimately causing the death of the targeted insect. RNAi is very effective against pest insects; however, its proficiency varies significantly among insect species, tissues, and genes. The coleopteran forest insects are susceptible to RNAi and can be the initial target, but we lack practical means of delivery, particularly in systems with long-lived, endophagous insects such as the Emerald ash borer, Asian longhorn beetles, and bark beetles. The widespread use of RNAi in forest pest management has major challenges, including its efficiency, target gene selection, dsRNA design, lack of reliable dsRNA delivery methods, non-target and off-target effects, and potential resistance development in wood-boring pest populations. This review focuses on recent innovations in RNAi delivery that can be deployed against forest pests, such as cationic liposome-assisted (lipids), nanoparticle-enabled (polymers or peptides), symbiont-mediated (fungi, bacteria, and viruses), and plant-mediated deliveries (trunk injection, root absorption). Our findings guide future risk analysis of dsRNA-based forest protection products (FPPs) and risk assessment frameworks incorporating sequence complementarity-based analysis for off-target predictions. This review also points out barriers to further developing RNAi for forest pest management and suggests future directions of research that will build the future use of RNAi against wood-boring coleopterans.